A psychometric study of the Flourishing Scale for people living with dementia - Chris Clarke; Kalpita Baird; Esme Moniz‐Cook; Gail Mountain; Emma Wolverson; Ellen Lee; Catherine Hewitt (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION There are few validated strengths‐based outcome measures for evaluations of psychosocial interventions in dementia and measurement of the concept of flourishing has not been directly explored. This study therefore examined the psychometric properties of the Flourishing Scale (FS)—an eight‐item generic self‐report measure of social‐psychological well‐being—and how it might be adapted for people with dementia. METHOD A secondary data analysis of baseline data from the Journeying Through Dementia study, a randomized controlled trial of a self‐management intervention for older adults with dementia living in the community in the United Kingdom (n = 480). Confirmatory Factor Analysis (CFA), Item Response Theory (IRT) analyses, and convergent/discriminatory analyses were undertaken. RESULTS Moderate negative skew in total FS scores was noted and adjusted for. A good level of internal consistency reliability was evident (alpha = 0.83). Both CFA and IRT analyses verified the unidimensionality of the scale and there was evidence of item discrimination. Measurement precision appeared greater for lower to moderate levels of well‐being, with some item‐level variation. Total FS scores were significantly associated with quality of life, self‐efficacy, and mood, supporting convergent validity. FS total scores were not associated with cognitive ability or time since diagnosis in this sample but were associated with living alone / with others. DISCUSSION These findings offer new avenues for strengths‐based research and practice of psychosocial interventions for people with dementia in relation to the measurement social‐psychological well‐being. The FS shows promise as a valid and reliable self‐report instrument for people with early‐stage dementia but further validation research is needed to confirm optimum item content and responsiveness. The measurement of well‐being of people living with moderate to severe cognitive impairments requires further research. Highlights Previous work suggests that well‐being in dementia could align with the concept of flourishing—optimized social‐psychological well‐being—but valid and reliable measurement of flourishing in dementia has not yet been directly explored. The aim of this study was to investigate the psychometric properties of the Flourishing Scale, a brief measure of social‐psychological well‐being previously validated with older people and cross‐culturally, for people living with dementia. We carried out a secondary analysis of baseline data (n = 480) from a previous randomized controlled trial of a self‐management psycho‐social intervention in dementia (the Journeying Through Dementia trial). Participants were living with early‐stage dementia, were predominantly White/British, and 57.8% were male. We utilized Classical Test Theory and Item Response Theory methods to examine the reliability, uni‐dimensionality, and validity of the Flourishing Scale as well as item characteristics. Findings indicate the Flourishing Scale is uni‐dimensional and has adequate internal consistency and validity for measuring social‐psychological well‐being in dementia. The scale can discriminate between different levels of well‐being in dementia, particularly at lower to moderate levels. Items concerned with active engagement appear most sensitive to measured levels of flourishing overall. People with dementia living alone may be most at risk of lower levels of social‐psychological well‐being. Levels of flourishing were not correlated with cognitive impairment. The Flourishing Scale measures eudaimonic dimensions of well‐being and may be of value in future dementia studies focused on these. The measurement precision of the Flourishing Scale for people with dementia may be best at low‐moderate levels and items may vary somewhat in terms of ability to discriminate levels of well‐being. Further research should explore optimum item content and response format and investigate how reliable and valid the instrument is longitudinally and for people living with a range of cognitive impairments at different stages of dementia.